Sarcocystis halieti Gjerde & Vikøren & Hamnes 2018 ... - Gjerde, Bjørn; Vikøren, Turid; Hamnes, Inger Sofie (Zenodo, 2018)
3.3.2. Ribosomal DNA unit of S. halieti As stated above, one species from the sea eagle, which we have named S. halieti, showed a high identity with GenBank sequences JQ733511–JQ733513 of an unnamed species from the great cormorant in Lithuania (unpublished study by Prakas and co-workers), and is considered to be identical with that species. As regards the complete 18S rRNA gene, which was 1803 bp long, the new sequence (GenBank no. MF 946587) was 100% identical with GenBank sequence JQ733511 from the great cormorant, but it was also completely identical with sequences of Sarcocystis wobeseri (GenBank nos. GQ 922885, GQ922886, HM 159419, EU502869). Moreover, the new sequence of S. halieti differed at only one nucleotide position (A rather than G in position 9 from the 3′ end) from GenBank sequence GQ245670 of S. calchasi, but this difference seems to be due to the inclusion of the terminal reverse primer (Primer B) in that sequence (Olias et al., 2010b). This primer does not match sequences of various ... : Published as part of Gjerde, Bjørn, Vikøren, Turid & Hamnes, Inger Sofie, 2018, Molecular identification of Sarcocystis halieti n. sp., Sarcocystis lari and Sarcocystis truncata in the intestine of a white-tailed sea eagle (Haliaeetus albicilla) in Norway, pp. 1-11 in International Journal for Parasitology: Parasites and Wildlife 7 (1) on page 6, DOI: 10.1016/j.ijppaw.2017.12.001, http://zenodo.org/record/10835073 ...